Population structure and reproduction of Mimagoniates microlepis with a new hypothesis of ontogenetic migration: implications for stream fish conservation in the Neotropics - Braga, Raul Rennó; Braga, Marcelo Rennó; Vitule, Jean Ricardo Simões (Environmental biology of fishes, 2013)
Longitudinal size segregation and reproductive aspects of Mimagoniates microlepis were studied along the catchment of the Piraquara River, a tributary of the Iguaçu River. Monthly fish sampling were completed at four sites along a longitudinal gradient. In addition, we summarized and compared key species-ecological traits of three different populations of this species. Data from the two additional populations were obtained from the literature. Our findings concerning population structure and reproduction of this species demonstrate that ontogenetic migration occurs within this population. During flash floods small individuals (C1) are carried to downstream habitats (P1). As they grow, we assume that their swimming capacity tends to increase and they are able to explore upstream habitats. This ontogenetic migration dynamic is a common and underexplored pattern for small stream fish in the Neotropics, and it helps to ensure, as a consequence, the long term persistence of the population along the entire hydrographic basin. Therefore, the alteration of only one portion of the river can compromise the entire migration process and consequently the entire population. In addition, the present study is the only source of ecological information for this population from before the recent construction of the Piraquara II dam. This reinforces the urgent need for conservation strategies for this population of M. microlepis and other similar populations or species.